An investigation of potential prognostic indicators and biomarkers (TRAF1, NF- kB and CD14) in renal cancers / Yap Ning Yi - Yap, Ning Yi (2018)
The incidence of renal cell carcinoma (RCC) is rising annually worldwide and around 30% of patients have metastasis at diagnosis. Once metastasized, RCC is treatment resistant with poor prognosis and a 5 year survival rate of 10-20%, even with treatment of targeted therapies. Currently, there are no suitable biomarkers being used in the routine diagnosis or prognostication of RCC in the clinical setting. A better understanding of dysregulated genes or proteins in RCC helps unravel the molecular complexities which contribute to tumour growth or progression. This enables the improvement of targeted therapies and identifies potential diagnostic or prognostic markers for the monitoring of RCC progression. Therefore, the general aim was to determine the clinical characteristics and protein biomarkers that could be potential diagnostic or prognostic indicators in RCC. Currently there is no comprehensive registry on RCC patients in Malaysia, hence the first objective was to determine the clinical characteristics and factors affecting survival of RCC patients in University Malaya Medical Centre. In this cohort of patients, TNM staging and palpable abdominal mass were independent predictors for survival. The clinical data gathered was also used in subsequent chapters for prognostic analyses. The proteins of interests were TRAF1 and NF-κB subunits (p50, p52, p65 and cRel), which are linked in pathways regulating cell survival, apoptosis and proliferation. The second and third objectives were to assess the prognostic significance of TRAF1 and NF-κB as biomarkers in RCC and the roles they play in controlling cell apoptosis/proliferation. The concentration of TRAF1 in clear cell RCC (ccRCC) patients’ serum and controls were determined using ELISA iv analysis. TRAF1 levels were significantly higher in ccRCC serum compared to controls. TRAF1 serum concentration was higher in metastatic patients compared to localised RCC. TRAF1 and NF-κB immunopositivity was also evaluated in RCC tissue. TRAF1 expression was significantly lower in ccRCC compared to the adjacent normal tissue, and was not associated with prognostic factors. Immunopositivity of p65 was higher in RCC compared to normal kidney tissue, but p50, p52 and cRel expressions were lower in RCC tissue. In tumour tissue, higher p52 and p65 expressions were associated with a worse survival outcome, hence they could be possible prognostic indicators in RCC. RCC cell line experiments revealed that TRAF1 silencing increased pro-survival cIAP-1 and cIAP-2 protein levels while p65 silencing decreased protein concentration of proliferation proteins, cyclin D1 and IL-6. The combination of low TRAF1 and high NF-κB p65 concentration in RCC tissue might cause an imbalance in cell proliferation and apoptosis, promoting tumour growth. The final objective was the discovery of additional serum biomarker in RCC. Isobaric tags for relative and absolute quantitation (iTRAQ) analysis identified CD14 as a potential prognostic marker as serum CD14 concentration was higher in ccRCC patients compared to controls and was significantly associated with stage. Further immunohistochemistry and functional studies using cell lines would aid in understanding the role of CD14 in RCC progression. In conclusion, TRAF1 and NF-κB were dysregulated in RCC tissue, and TRAF1 and CD14 were potential serum indicators for advanced RCC.